Macro and microangiopathy related to retinopathy and choroidopathy in type 2 diabetes. Issue 4 (July 2022) - de Asís Bartol-Puyal, Francisco; Isanta, Carlos; Calvo, Pilar; Abadía, Beatriz; Ruiz-Moreno, Óscar; Pablo, Luis
Purpose: To describe the relationship between diabetic retinopathy (DR) and choroidal thickness (CT), and systemic macro and microangiopathy in patients with type 2 diabetes (T2D). Methods: Cross-sectional study enrolling 200 eyes (100 T2D naïve patients) without macular edema. DR was graded and swept-source optical coherence tomography Triton DRI (Topcon) was used to measure CT, which gave automatic measurements in ETDRS grid. An endocrinologist examined all the patients and searched in their medical records for data about macro and microangiopathy: ischemic cardiopathy (IC), cerebrovascular accident (CVA), peripheral artery disease (PAD), nephropathy, and peripheral polyneuropathy (PPN). Results: Mean age was 67.38 ± 8.15 years, mean axial length was 23.26 ± 0.09 mm, and mean IOP was 16.75 ± 3.06 mmHg. Sixty eyes had no DR, 46 had mild, 64 had moderate, 20 had severe, and 10 had proliferative DR. IC was correlated with horizontal choroidal zones ( p  < 0.05 and η between 0.16 and 0.21) but not with DR ( p  = 0.16). CVA was neither correlated with CT ( p  > 0.05) nor with DR ( p  = 0.39). PAD was not correlated with CT ( p  > 0.05) but it was with DR ( p  = 0.03). The type of nephropathy was correlated both with CT in vertical sectors ( p  < 0.05 and η between 0.15 and 0.27) and DR ( p  = 0.01, τ = 0.24). PPN was not correlated with CT ( p  > 0.05) but it was with DR ( p  = 0.03). Conclusions: DR is correlated with microangiopathy (nephropathy and PPN) but not with macroangiopathy (IC, CVA, and PAD). CT is mildly correlated with nephropathy and IC. Some choroidal regions are more sensitive than others to each diabetic macro and microvascular manifestation.